A CORRECTNESS BEHAVIOUR IN THE CONTEXT OF MULTICULTURAL SOCIETY - Ifham Choli (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2021)
A Correctness behaviour is a guidance from Islamic Religion. The flexibility of Islamic religion is seen from its doctrinal aspect which emphasizes convenience, good behaviour, and moderation allowing the religion to coexist in a multicultural community entity, such as in Indonesia. The ability of the people in accepting new values that come from outside their communities is a multicultural experience that is difficult to match. Indonesian Islam is of course formed in a multicultural atmosphere that is almost without the slightest contradiction. Differences in language, tradition, culture, communal values, and even religions and beliefs, are integrated into a religious life that is unique and too difficult to separate. For people who can understand the existence of religion from a socio-historical perspective, religious teachings that have given birth to new traditions in that society are proof that religion does not reject tradition as a whole. On the other hand, religion can provide space for local values that are considered good. Religion that has entered a multicultural society will experience an acculturation process so that religion can have many versions, especially in the aspect of implementation, from the perspective of understanding to the importance of religion in accordance with the culture of each region or place. From this multicultural society, differences in expression were born in carrying out religious orders. Correctness behaviour to create a multicultural society can be done by forming a harmonious community, intertwining together to build a religious community, so that what is later called as a form of Islamic civilization comes from a background of different traditions in society, but is able to integrate politically into a community. Multicultural community through ties of faith that transcend their religious boundaries. Perilaku Ihsan adalah pedoman dari Agama Islam. Fleksibilitas agama Islam dilihat dari aspek doktrinalnya yang mengedepankan kenyamanan, perilaku yang baik, dan moderasi yang memungkinkan agama tersebut hidup berdampingan dalam entitas masyarakat yang multikultural, seperti di Indonesia. Kemampuan masyarakat dalam menerima nilai-nilai baru yang datang dari luar komunitasnya merupakan pengalaman multikultural yang sulit ditandingi. Islam Indonesia tentunya terbentuk dalam suasana multikultural yang nyaris tanpa kontradiksi sedikitpun. Perbedaan bahasa, tradisi, budaya, nilai komunal, bahkan agama dan kepercayaan, diintegrasikan ke dalam kehidupan beragama yang unik dan terlalu sulit dipisahkan. Bagi masyarakat yang dapat memahami keberadaan agama dari perspektif sosio-historis, ajaran agama yang melahirkan tradisi baru dalam masyarakat tersebut merupakan bukti bahwa agama tidak menolak tradisi secara keseluruhan. Di sisi lain, agama bisa memberi ruang bagi nilai-nilai lokal yang dianggap baik. Agama yang telah memasuki masyarakat multikultural akan mengalami proses akulturasi sehingga agama dapat memiliki banyak versi terutama dalam aspek pelaksanaannya, mulai dari perspektif pemahaman hingga pentingnya agama sesuai dengan budaya masing-masing daerah atau tempat. Dari masyarakat multikultural inilah lahir perbedaan ekspresi dalam menjalankan tatanan agama. Perilaku kebenaran untuk mewujudkan masyarakat multikultural dapat dilakukan dengan membentuk masyarakat yang rukun, terjalin bersama untuk membangun masyarakat yang beragama, sehingga apa yang kemudian disebut sebagai wujud peradaban Islam berasal dari latar belakang tradisi yang berbeda-beda dalam masyarakat, namun mampu berintegrasi secara politik ke dalam komunitas. Komunitas multikultural melalui ikatan keimanan yang melampaui batas agama mereka.